Implementation of the 'Sekolah Sisan Ngaji (SSN)' Program at an Elementary School: A Study of Teaching Methods, Learning Activities, and Barriers - Muhammad Hafid Al Husain; Hery Setiyatna; Naili Mar'atil Fitriyah (At-Ta'lim : Media Informasi Pendidikan Islam, 2026)
ENGLISH: Implementation of the Sekolah Sisan Ngaji (SSN) Program at an Elementary School: A Study of Teaching Methods, Learning Activities, and BarriersPurpose: This study aimed to describe and analyze the implementation of the Sekolah Sisan Ngaji (SSN) Program at SDN 1 Todanan, Blora Regency. Method: A qualitative single-case study design was employed. Data were collected through participatory observation, semi-structured interviews, and document analysis and were analyzed using the Miles, Huberman, and Saldaña interactive model. Results: The SSN Program was implemented as a standalone subject using the UMMI method, peer tutoring, and lecture-discussion approaches. Learning activities included Qur’anic literacy, tajwid instruction, memorization of short surahs, daily prayers, and religious habituation. Seven sixth-grade students successfully memorized the entire Juz 30 in 2026. Major barriers included an unfavorable teacher–student ratio, limited Qur’an availability, and insufficient time for individualized instruction. Conclusion: A structured curriculum, appropriate teaching methods, and a strong religious culture supported successful Qur’anic learning despite limited resources. Contribution: This study provides an empirical model for implementing local Islamic education policies in resource-constrained elementary schools.INDONESIAN: Implementasi Program Sekolah Sisan Ngaji (SSN) di Sekolah Dasar: Kajian Metode Pembelajaran, Aktivitas Pembelajaran, dan Faktor PenghambatTujuan: Penelitian ini bertujuan mendeskripsikan dan menganalisis implementasi Program Sekolah Sisan Ngaji (SSN) di SDN 1 Todanan, Kabupaten Blora. Metode: Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus tunggal. Data dikumpulkan melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldaña. Hasil: Program SSN dilaksanakan sebagai mata pelajaran mandiri dengan metode UMMI, tutor sebaya, serta ceramah dan tanya jawab. Aktivitas pembelajaran mencakup baca tulis Al-Qur’an, tajwid, hafalan surah pendek, doa harian, dan pembiasaan religius. Sebanyak tujuh siswa kelas VI berhasil menghafal Juz 30 pada tahun 2026. Hambatan utama meliputi rasio guru-siswa yang tidak ideal, keterbatasan Al-Qur’an, dan waktu bimbingan individual yang terbatas. Kesimpulan: Kurikulum terstruktur dan budaya religius mendukung keberhasilan pembelajaran Al-Qur’an meskipun sumber daya terbatas. Kontribusi: Penelitian ini menyediakan model empiris implementasi kebijakan pendidikan Islam lokal bagi sekolah dasar dengan keterbatasan sumber daya.